Host specificity and species diversity in communities of frugivorous insect in lowland rain forest of Papua New Guinea - Čtvrtečka, Richard (Jihočeská univerzita, 2015)
The thesis describes host specificity and species diversity in communities of frugivorous insect in lowland rain forest of Papua New Guinea. It focuses separately on weevils and Lepidoptera, as main groups of frugivores. Further, it focuses on fruit morphology and the structure of frugivorous communities.
Host specificity and species diversity in communities of frugivorous insect in lowland rain forest of Papua New Guinea